Analisis Pengaruh Modal Kerja, Pendapatan, Biaya Operasional, Dan Arus Kas Operasi Terhadap Laba Bersih Perusahaan Sektor Aneka Industri Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019 - Sinta Risma Indriyani; Hadi Samanto; Suprihati Suprihati (ITB AAS INDONESIA, 2022)
Abstract The purpose of this study was to determine the effect of working capital, income, operating cost, and operating cash flow on the net profit. The object of this study are companies from miscellaneous industrial sectors listed in the Indonesia Stock Exchange during 2017 to 2019. Type of data use secondary data sourced from financial reports from the official website www.idx.co.id. The sample selection used purposite sampling method with a population of 50 companies in miscellaneous industrial sectors listed in the Indonesia Stock Exchange that met the sample criteria of 16 companies. The analytical method used in this research is multiple linear regression with the help of IBM SPPS Software. The results showed that working capital, income, operating cost, and operating cash flow simultaneously gave an effect of 80,2% in determining the amount of net profit. Partially shows that working capital and cash flow have a significan effect on the company’s net income. Meanwhile, income and operating cost have no significan effect on income. keyword: Working Capital, Income, Operating Cost, Operating Cash flow, Net Profit